Der pseudocyprianische Tractat "De Aleatoribus" die älteste lateinische-christliche Schrift, ein Werk des römischen Bischofs Victor II (saec[ulum] II (Classics in the History of Early Christian Literature, 2010)
One of the first pieces of Christian Latin, a treatise on the evils of gambling and the role of the bishop in correcting them